The duke with the dragon tattoo eaudiobook - Byrne, Kerrigan (Victorian Rebels, 2018)
The bravest of heroes. The brashest of rebels. The boldest of lovers. These are the men who risk their hearts and their souls—for the passionate women who dare to love them . . . He is known only as The Rook. A man with no name, no past, no memories. He awakens in a mass grave, a magnificent dragon tattoo on his muscled forearm the sole clue to his mysterious origins. His only hope for survival—and salvation—lies in the deep, fiery eyes of the beautiful stranger who finds him. Who nurses him back to health. And who calms the restless demons in his soul . . . A LEGENDARY LOVE Lorelai will never forget the night she rescued the broken dark angel in the woods, a devilishly handsome man who haunts her dreams to this day. Crippled as a child, she devoted herself to healing the poor tortured man. And when he left, he took a piece of her heart with him. Now, after all these years, The Rook has returned. Like a phantom, he sweeps back into her life and avenges those who wronged her. But can she trust a man who's been branded a rebel, a thief, and a killer? And can she trust herself to resist him when he takes her in his arms?